Pandemin som strålkastare — Skörhet, samspel och (o)självständighet som deltagarideal i folkhögskolan - Alexandra Söderman; Filippa Millenberg (Educare)
This article focuses on the participant ideals that emerged in the Swedish folkhögskola (‘adult education folk high school’) during the COVID-19 pandemic, when most of these schools’ activities transitioned to distance learning following the restrictions imposed by the Public Health Agency of Sweden. The study is based on empirical material from two different studies conducted during this period. One study employed an ethnographic method, while the other included surveys and focus group interviews with teachers. The aim is to examine the student participant ideals that emerge in adult education folk high school teachers’ accounts of their work during the pandemic, guided by the following research question: What participant ideals emerge in folk high school teachers’ accounts of their work during the COVID-19 pandemic and around which values do these take shape? Drawing on concepts from Pierre Bourdieu, the study analyses the representations and ideals that appear in teachers’ statements about course participants in relation to the pandemic. The results show that values such as fragility and ability to interact were largely recognized as symbolic participant capital by teachers during the pandemic, whereas independence was both recognized and misrecognized. The study contributes both to research on adult education folk high schools during the pandemic and to research on student participant ideals in these schools.